Gambaran Posisi Kerja dan Keluhan Musculoskeletal Disorder (MSDs) pada Pekerja di Industri Baja Gresik - Saikhunuddin; Noeroel Widajati; Indriati Paskarini (Universitas Airlangga, 2024)
Background: One of the occupational health and safety problems that many manufacturing workers experience is unergonomic work positions, this can cause fatigue and several serious diseases, including Musculoskeletal Disorder (MSDs.) Objectives: To find out the description of work positions and MSD complaints felt by workers of Gresik Steel Industry, particularly in the area of magnetic flux leakage and rework. Methods: This study used an observational method and analysis was carried out using the Angle Meter application, Rapid Entire Body Assessment (REBA), and the Nordic Body Map (NBM) questionnaire. Results: The assessment of work positions shows that 2 workers have a moderate risk level, 4 workers have a high risk level, and 2 workers have a very high risk level that requires immediate improvement. The results of observations show that the work activities that are often carried out by workers are squatting positions with a bent back and neck in a flexed position, which is an unergonomic position. A total of 87.5% of workers experienced moderate MSDs complaints, and 12.5% of workers experienced low-level MSDs complaints. Control efforts that have been made include the use of tools to lift products, setting working hours and breaks, and using personal protective equipment (PPE). Conclusion: Assessment of work positions in magnetic flux leakage and rework area workers has a high risk level that requires immediate corrective action, and MSDs complaints are felt by workers in the high category. The description of work positions can be used as a basic reference for companies to determine additional control efforts to reduce the risk of MSDs complaints among workers in the future.